Analisis Prosedur Pemberian Kredit Untuk Mencegah Kredit Macet Pada Lembaga Perkreditan Desa (LPD) Desa Adat Kedisan Kecamatan Tegallalang - Yani, Ni Putu Linda; Putra, I Putu Deddy Samtika; Muliati, Ni Ketut (Hita Akuntansi dan Keuangan, 2025)
LPDs have a strategic role in providing access to credit to rural communities, which are often difficult to reach by formal financial institutions.One of the objectives of LPDs is to improve community welfare through the provision of credit tailored to local needs.However, in recent years, serious problems have emerged related to the increasing number of non-performing loans in LPDs.Non-performing loans can threaten the continuity of LPD operations reduce liquidity, and ultimately affect the overall financial stability of the LPD. The research team at Kedisan Traditional Village's Village Credit Institution (LPD) set out to find out how they avoid bad debts while extending credit. In this study, comparative descriptive analysis was used as an analytical tool. Specifically, the researcher compared the theoretical procedures for awarding credit with the results obtained from data collected through observation at the object of research. It is clear from the interview results that LPD Desa Adat Kedisan's credit granting procedures are theoretically sound; however, in practice, the LPD makes errors during the credit analysis stage, when it incorrectly evaluates the customer's character and the collateral.Some things that can be done by Kedisan LPD are repeated checks of the requirements given by prospective customers and being more careful in the assessment so that there are no repeated mistakes and the need to carry out ongoing training for LPD staff to improve credit analysis skills, and increase socialization to the community about financial management and the importance of paying credit on time.